1999
DOI: 10.1126/science.285.5426.384
|View full text |Cite|
|
Sign up to set email alerts
|

Worlds Apart? The Reception of Genetically Modified Foods in Europe and the U.S.

Abstract: Recent controversies about genetically modified foods in the United Kingdom and several other European countries highlight the apparent differences that exist in public opinion on this subject across the Atlantic. Why are people in the United States seemingly untroubled by a technology that causes Europeans so many difficulties? The results of survey research on public perceptions of biotechnology in Europe and the United States during 1996-1997, together with an analysis of press coverage and policy formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
329
3
12

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(353 citation statements)
references
References 1 publication
9
329
3
12
Order By: Relevance
“…( Davison et al, 1997;Gaskell et al, 1999;Bonfadelli, 2005). Although higher knowledge has been associated with positive attitudes toward genetic testing (Davison et al, 1997;Rose et al, 2005), we found little or no relationship between knowledge and attitudes, comporting with other published findings (Macnicol et al, 1991;Singer, 1991;Decruyenaere et al, 1992).…”
Section: Discussionsupporting
confidence: 50%
“…( Davison et al, 1997;Gaskell et al, 1999;Bonfadelli, 2005). Although higher knowledge has been associated with positive attitudes toward genetic testing (Davison et al, 1997;Rose et al, 2005), we found little or no relationship between knowledge and attitudes, comporting with other published findings (Macnicol et al, 1991;Singer, 1991;Decruyenaere et al, 1992).…”
Section: Discussionsupporting
confidence: 50%
“…Polarisation works well in the media. Media coverage, and a diminished public trust in regulatory authorities may explain why GM crops have met rancorous public resistance in Europe (Gaskell et al, 1999;PABE, 2001). There seems a current tendency in Western societies to take the bearers of bad news more seriously than the bearers of good news.…”
Section: Discussionmentioning
confidence: 99%
“…The higher acceptance of genetically modified foods and feeds in North America compared to Europe [5] is demonstrated by the fact, that two thirds of GM corn cultivations in this region are genetically modified plants, whereas in Europe, GM plants make a minor proportion only. The public needs to be placed in a position to make qualified decisions, and politicians must take the lead in the societal discourse and assume their responsibility.…”
Section: Transparent Communication Strategy On Gmosmentioning
confidence: 99%